HUBUNGAN NEUROPATI PERIFER DENGAN KADAR CD4 PADA PASIEN HIV/AIDS YANG MENDAPAT TERAPI ANTIRETROVIRAL DI RSUP DR. M. DJAMIL PADANG - Dwitri Achda Ichromi; Yuri Haiga; Dhina Lydia Lestari (Yayasan Nusantara Hasana Berdikari, 2025)
Peripheral neuropathy is damage to the nerves that transmit signals in the brain and spinal cord. Peripheral neuropathy is a common condition that occurs in HIV/AIDS patients who have taken antiretroviral drugs. HIV/AIDS patients will experience decreased CD4 levels due to a weakened immune system. This research objective to determine the relationship between peripheral neuropathy disorders and CD4 levels in People With HIV/AIDS (PLWHA) with antiretroviral therapy at Dr. M. Djamil Padang General Hospital. The fields of internal medicine and neurology are the focus of this study. This study was conducted in November 2024. This study is a categorical comparative analysis. The accessible study population is all PLWHA who receive antiretroviral treatment at Dr. M. Djamil Padang General Hospital who have peripheral neuropathy problems. A total of 49 people were sampled using sequential sampling techniques. Frequency distribution is used to show univariate data analysis, while the chi-square test is used for bivariate analysis. IBM 26.0 is a computerized SPSS application used for data processing. Most patients had category III CD4 levels, namely 31 people (63.3%), experienced mild peripheral neuropathy disorders, namely 43 people (87.8%), received TLD ARV drugs as many as 37 people (75.5%). There was a relationship between CD4 levels and peripheral neuropathy disorders in People With HIV/AIDS (PLWHA) with antiretroviral therapy (p = 0.034). There was no relationship between CD4 levels and peripheral neuropathy disorders in People With HIV/AIDS (PLWHA) with antiretroviral therapy at Dr. M. Djamil Padang General Hospital (p= 0.300). There was a relationship between peripheral neuropathy disorders and CD4 levels and no relationship between ARV types and peripheral neuropathy disorders in People With HIV/AIDS (PLWHA) with antiretroviral therapy at Dr. M. Djamil Padang General Hospital.